2019
DOI: 10.1111/trf.15332
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of yellow fever virus in plasma after treatment with methylene blue and visible light and in platelet concentrates following treatment with ultraviolet C light

Abstract: BACKGROUND: Yellow fever virus (YFV) is endemic to tropical and subtropical areas in South America and Africa, and is currently a major public health threat in Brazil. Transfusion transmission of the yellow fever vaccine virus has been demonstrated, which is indicative of the potential for viral transfusion transmission. An approach to manage the potential YFV transfusion transmission risk is the use of pathogen inactivation (PI) technology systems, such as THERAFLEX MB-Plasma and THERAFLEX UV-Platelets (Macop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In addition, while platelets are resuspended in PAS in Europe and in PAS or in 100% plasma in North America, in Latin America, which is most impacted by YFV outbreaks, platelet manufacturing is in 100% plasma, and this is the first demonstration of PR technology to inactivate YFV in PC‐Plasma. A previous study by Faddy et al reported YFV‐17D inactivation levels of greater than 4.77 log in plasma treated with the THERAFLEX MB‐Plasma system and greater than 4.8 log in PC resuspended in 30% plasma/70% PAS treated with THERAFLEX UV‐Platelets. We report here higher levels of inactivation using the INTERCEPT Blood System for platelets, which is currently used routinely in more than 30 countries and has been reported to be efficacious at inactivating other arboviruses that often cocirculate in impacted areas.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, while platelets are resuspended in PAS in Europe and in PAS or in 100% plasma in North America, in Latin America, which is most impacted by YFV outbreaks, platelet manufacturing is in 100% plasma, and this is the first demonstration of PR technology to inactivate YFV in PC‐Plasma. A previous study by Faddy et al reported YFV‐17D inactivation levels of greater than 4.77 log in plasma treated with the THERAFLEX MB‐Plasma system and greater than 4.8 log in PC resuspended in 30% plasma/70% PAS treated with THERAFLEX UV‐Platelets. We report here higher levels of inactivation using the INTERCEPT Blood System for platelets, which is currently used routinely in more than 30 countries and has been reported to be efficacious at inactivating other arboviruses that often cocirculate in impacted areas.…”
Section: Discussionmentioning
confidence: 93%
“…These results are similar to studies with other arboviruses, in which infectivity of DENV was reduced by at least 4.46 log, CHIKV by at least 6.58 log , ZIKV by at least 5.68 log, and YFV by at least 4.77 log. 11,13,14 F I G U R E 1 JEV plaque formation before and after treatment with the THERAFLEX systems detected by immunoplaque assay on Vero cells. Representative plaques formed by JEV at 1:10 viral dilution in plasma treated with the THERAFLEX MB-Plasma system using different illumination doses (left) and in PCs treated with the THERAFLEX UV-Platelet system using different illumination doses We also show that on average, the THERAFLEX UV-Platelets system can reduce JEV infectivity in PCs by 7.02 log.…”
Section: Discussionmentioning
confidence: 99%
“…Only plasma and PCs that tested negative for JEV IgG and IgM were used, and these were treated as described previously. [11][12][13][14] PC quality control variables including platelet count, unit volume, swirl, and pH were assessed. 12,18 1.2 | Cell culture African green monkey kidney cells (Vero; ATCC# CCL-81) were grown in culture and treated as described previously.…”
Section: Blood Componentsmentioning
confidence: 99%
See 2 more Smart Citations